Outcomes from the iEMSs data mining in the environmental sciences workshop series - Gibert, K.; Sànchez-Marrè, M. (Environmental modelling & software : with environment data news, 2011)
The Data Mining for Environmental Sciences workshop series started inside iEMSs in 2006 and provides a valuable opportunity for close contact between KDD and Environmental community. After several editions of the workshop, possibilities of KDD for solving very complex environmental problems seems to be better understood by environmental scientists, whereas KDD scientists receive useful inputs to better understand environmental complexity and develop appropriate tools to provide useful responses to the current problems in the area. Some scientific conclusions of this interesting exchange are presented here.